Two new species of the genus Gunarus Des Gozis, 1886 (Coleoptera: Tenebrionidae: Helopini) from Southern Turkey - Nabozhenko, Maxim V.; Keskin, Bekir (Zootaxa, 2009)
Three species of the genus Gunarus (Coleoptera: Tenebrionidae: Helopini) are known from Turkey: G. lapidicola (Küster, 1850), G. gayirbegi sp. n. and G. korkutelensis sp. n. The species G. nodicornis Reitter, 1922 was described from Algeria (Takhat) and erroneously recorded from Turkey (Tokat). A key to the species of Gunarus of Turkey is provided.